Neutralizations in Retail Banking: A Qualitative Analysis. Issue 4 (3rd April 2017) - Leasure, Peter
ABSTRACT: This study seeks to examine neutralization theory's generalizability to other white collar crime contexts and also seeks to address the question of whether certain techniques of neutralization are more likely with certain kinds of white collar crime or offenders. These objectives are achieved through a case study of active members of the retail banking industry. Results indicate that neutralization theory does generalize to the retail banking context. Results also show that neutralization techniques identified in this sample relate more to corporate rather than occupational crime. Findings have implications for theoretical development and also for methods to combat white collar deviance.